Rights and Obligations of Children to Parents as Objects of Commercial Content on Tiktok According to the Marriage Law - Hana Yunita Wagimin; Waode Mustika (Estudiante Law Journal, 2023)
This study aims to find out how the rights and obligations of children towards parents as objects of commercial content on TikTok according to the marriage law. The research method used is normative. The results of the study show that the rights and obligations of children towards their parents are based on the Marriage Law; children must respect their parents and obey their good wishes. And if the child has grown up, he is obliged to look after according to his ability, parents and family in a straight line upwards, if they need help. Legal consequences for children who do not carry out their alimony obligations towards parents, namely parents can submit a determination to the District Court and file civil lawsuits regarding unlawful acts (PMH) committed by children due to non-fulfillment of children's obligations in providing care to parents whether it's looking after and caring for parents in a healthy or sick condition, as well as providing a living and other things, including the cost of compensation.